Putting Terror in Its Place: An Experiment on Mitigating Fears of Terrorism among the American Public. (February 2022) - Silverman, Daniel; Kent, Daniel; Gelpi, Christopher
An American's yearly chance of being killed by a terrorist attack sits at roughly 1 in 3.5 million. Yet, over 40 percent of Americans consistently believe that they or their family members are likely to be a terror victim. Can these inflated estimates of the risks of terrorism be brought closer to reality? With trillions of dollars spent on the "War on Terror, " this question is not just theoretically but practically important. In order to investigate, we use an experimental approach assessing whether people update their beliefs about terrorism when given factual information about the relative risks it presents. We find that public fear of terrorism and demand for countering it can be sharply reduced with better information, dropping essentially to pre-9/11 levels after the treatment and staying that way two weeks later. These results suggest that countering the indirect costs of terrorism may largely require providing more context and perspective.